2020
DOI: 10.3390/agronomy10111752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated CO2 on Tomato (Lycopersicon esculentum Mill.) Growth and Rhizosphere Soil Microbial Community Structure and Functionality

Abstract: Although elevated CO2 (eCO2) in the atmosphere is one of the main factors influencing climate and ecosystem stability, less research on eCO2 in greenhouse soil systems has been conducted, despite their prevalence. In this article, phospholipid fatty acid (PLFA) profiling, 16S rRNA and Internally Transcribed Spacer (ITS) gene sequencing and high-throughput quantity polymerase chain reactions (HT-qPCRs) for 72 biogeochemical cycling-related genes were used to reveal the comprehensive responses of microbes to 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
2
5
0
Order By: Relevance
“…During the 15 days of CO 2 fumigation, the absolute abundance of the total PLFAs was significantly ( p < 0.05) stimulated by eCO 2 treatment, while the overall microbial community structure (the PLFA profile) was not influenced by CO 2 concentration ( Figure 3 ), as confirmed by Adonis analysis and Mantel tests ( p > 0.05). The above results were similar to those of previous studies in which short-term eCO 2 fumigation usually led to increases in root rhizodeposition and microbial biomass [ 42 ] but had little influence on microbial community structure [ 27 , 43 , 44 ]. In fact, because of the differences in plant species, soil characteristics and experimental designs, the observed response of the microbial community structure to eCO 2 is not always the same [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…During the 15 days of CO 2 fumigation, the absolute abundance of the total PLFAs was significantly ( p < 0.05) stimulated by eCO 2 treatment, while the overall microbial community structure (the PLFA profile) was not influenced by CO 2 concentration ( Figure 3 ), as confirmed by Adonis analysis and Mantel tests ( p > 0.05). The above results were similar to those of previous studies in which short-term eCO 2 fumigation usually led to increases in root rhizodeposition and microbial biomass [ 42 ] but had little influence on microbial community structure [ 27 , 43 , 44 ]. In fact, because of the differences in plant species, soil characteristics and experimental designs, the observed response of the microbial community structure to eCO 2 is not always the same [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…The above results were similar to those of previous studies in which short-term eCO 2 fumigation usually led to increases in root rhizodeposition and microbial biomass [ 42 ] but had little influence on microbial community structure [ 27 , 43 , 44 ]. In fact, because of the differences in plant species, soil characteristics and experimental designs, the observed response of the microbial community structure to eCO 2 is not always the same [ 27 ]. A study conducted in a grassland revealed that even a longer period of eCO 2 fumigation produced no effect on the microbial community structure [ 45 ], which might be attributed to the specific ecosystem involved and the large pool of soil carbon underground.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations